2011
DOI: 10.1111/j.1759-6831.2011.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Population differentiation and phylogeographic pattern of a relict species, Conandron ramondioides (Gesneriaceae), revealed from sequence polymorphism and haplotypes of the CYCLOIDEA gene

Abstract: Historical events are expected to affect population genetic differentiation and DNA molecular evolution, but the impact of these effects remains a matter of debate. Here, for Conandron ramondioides (Gesneriaceae), we analyzed the genetic structure and phylogeographical pattern of 248 individuals from 13 populations, distributed in mainland China and Taiwan Island, based on the nucleotide sequence and haplotype of the coding sequence of CYCLOIDEA1 (GCYC1). Among the populations, we found a high level of haploty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Similarly in northern and northeast China, phylogeographic studies suggest regional expansions and multiple glacial refugia for a limited number of species with glacial refugia being sparsely located in the mountains from the north to the south (e.g., Chen et al, 2008a; Du et al, 2009; Tian et al, 2009; Bai et al, 2010; Guo et al, 2010; Ren et al, 2011; Zeng et al, 2011; An et al, 2012). However, in middle, southern and southeast China, regional expansions were found rarely and only local expansions occurred in the studied species (e.g., Su et al, 2005; Wang & Ge, 2006; Gao et al, 2007; Yan et al, 2007; Qiu et al, 2009a, 2009b; Wang et al, 2009a; Zhou et al, 2010; Chen et al, 2012; Li et al, 2012c; Peng et al, 2012; Xiao et al, 2012; Xie et al, 2012). Despite the quantity of phylogeographic studies not being homogeneous among different regions and different plant groups in China, multiple glacial refugia seem to be a general rule for most species studied (see Qiu et al, 2011).…”
Section: Phylogeographic Patterns Of Plants In Chinamentioning
confidence: 83%
“…Similarly in northern and northeast China, phylogeographic studies suggest regional expansions and multiple glacial refugia for a limited number of species with glacial refugia being sparsely located in the mountains from the north to the south (e.g., Chen et al, 2008a; Du et al, 2009; Tian et al, 2009; Bai et al, 2010; Guo et al, 2010; Ren et al, 2011; Zeng et al, 2011; An et al, 2012). However, in middle, southern and southeast China, regional expansions were found rarely and only local expansions occurred in the studied species (e.g., Su et al, 2005; Wang & Ge, 2006; Gao et al, 2007; Yan et al, 2007; Qiu et al, 2009a, 2009b; Wang et al, 2009a; Zhou et al, 2010; Chen et al, 2012; Li et al, 2012c; Peng et al, 2012; Xiao et al, 2012; Xie et al, 2012). Despite the quantity of phylogeographic studies not being homogeneous among different regions and different plant groups in China, multiple glacial refugia seem to be a general rule for most species studied (see Qiu et al, 2011).…”
Section: Phylogeographic Patterns Of Plants In Chinamentioning
confidence: 83%
“…Conandron ramondioides is another relic and paleoendemic genus in East Asia which is also apparently evolved as an actinomorphic reversal from zygomorphic ancestor (Kokubugata and Peng 2004 ; Wang et al 2010 ; Xiao et al 2012 ). Like R. myconi , its corolla tube is lost and five petals are equally large with five stamens fully developed.…”
Section: Introductionmentioning
confidence: 99%
“…The isolated nature of C. ramondioides habitats (moist rocks) is enhanced by recent human disturbance, including the tourism activities and hydropower development observed in many populations (Wang, 2004; Xiao, 2005; Wang et al, 2010). All these factors combined compromise successful pollination and seed germination, thereby accelerating the rate of genetic erosion within populations via increased inbreeding and genetic drift (Young et al, 1996; Hsin & Wang, 2018), as well as promoting genetic differentiation among populations and regions (Xiao et al, 2012). ADMIXTURE analysis, PCA, and the phylogenetic tree all indicate that there are three distinct genetic lineages within C. ramondioides , which correspond to the three main regions where the species is present, that is, mainland China, Taiwan Island, and Japan (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2B). Hsin (2019), using single‐copy nuclear markers, also identified these three genetic clusters, whereas Xiao et al (2012) also found two genetic clusters for China (i.e., mainland China and Taiwan Island) with the CYCLOIDEA1 (GCYC1) coding sequence. The clear genetic clustering pattern, which has a strong geographic basis, together with a significant positive correlation between genetic distance and geographic distance at the population level ( r = 0.499, P = 0.01; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation